2003
DOI: 10.1074/jbc.m210566200
|View full text |Cite
|
Sign up to set email alerts
|

Identification by Mutagenesis of Conserved Arginine and Glutamate Residues in the C-terminal Domain of Rat Liver Carnitine Palmitoyltransferase I That Are Important for Catalytic Activity and Malonyl-CoA Sensitivity

Abstract: Carnitine palmitoyltransferase I (CPTI) catalyzes the conversion of long chain fatty acyl-CoAs to acylcarnitines in the presence of L-carnitine. To determine the role of the conserved glutamate residue, Glu-603, on catalysis and malonyl-CoA sensitivity, we separately changed the residue to alanine, histidine, glutamine, and aspartate. Substitution of Glu-603 with alanine or histidine resulted in complete loss of L-CPTI activity. A change of Glu-603 to glutamine caused a significant decrease in catalytic activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
(44 reference statements)
1
10
0
Order By: Relevance
“…For M-CPTI, our mutagenesis studies demonstrate that in addition to Glu-3 and His-5, Val-19, Leu-23, and Ser-24 are necessary for malonylCoA inhibition and high affinity binding, in agreement with the differences in malonyl-CoA sensitivity observed between M-CPTI and L-CPTI (17,18). In addition, our site-directed mutagenesis studies of conserved residues in the C-terminal domain of L-CPTI demonstrated that conserved arginine and glutamate residues are important for catalytic activity and malonyl-CoA sensitivity (19,23). Others have reported that the deletion of N-terminal residues 19 -30 containing Ser-24 and Gln-30 or substitution of Ser-24 and Gln-30 with alanine in L-CPTI increased malonyl-CoA sensitivity but their effect was entirely dependent on the presence of Glu-3 because mutation of Glu-3 to alanine was found to override the effects of both the deletion and the combined effects of S24A and Q30A on malonyl-CoA sensitivity (28,29), confirming our previous report that Glu-3 in the extreme N-terminal region of L-CPTI is the main determinant of malonyl-CoA sensitivity (16).…”
Section: Glu-5903 Ala Mutant L-cpti With Increased Malonyl-coa Sensitsupporting
confidence: 66%
See 2 more Smart Citations
“…For M-CPTI, our mutagenesis studies demonstrate that in addition to Glu-3 and His-5, Val-19, Leu-23, and Ser-24 are necessary for malonylCoA inhibition and high affinity binding, in agreement with the differences in malonyl-CoA sensitivity observed between M-CPTI and L-CPTI (17,18). In addition, our site-directed mutagenesis studies of conserved residues in the C-terminal domain of L-CPTI demonstrated that conserved arginine and glutamate residues are important for catalytic activity and malonyl-CoA sensitivity (19,23). Others have reported that the deletion of N-terminal residues 19 -30 containing Ser-24 and Gln-30 or substitution of Ser-24 and Gln-30 with alanine in L-CPTI increased malonyl-CoA sensitivity but their effect was entirely dependent on the presence of Glu-3 because mutation of Glu-3 to alanine was found to override the effects of both the deletion and the combined effects of S24A and Q30A on malonyl-CoA sensitivity (28,29), confirming our previous report that Glu-3 in the extreme N-terminal region of L-CPTI is the main determinant of malonyl-CoA sensitivity (16).…”
Section: Glu-5903 Ala Mutant L-cpti With Increased Malonyl-coa Sensitsupporting
confidence: 66%
“…1). We have previously demonstrated that the conserved Glu-603 residue together with the two adjacent highly conserved arginine residues, Arg-601 and Arg-606, are important for L-CPTI activity and malonyl-CoA sensitivity (19,23).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this illustrates that residues located far from the catalytic residues in the primary amino acid sequence can in fact be crucial elements of the catalytic core. This also explains why deletion and/or mutation within the C terminus of CPT1A so dramatically affected initial protein folding and/or catalytic activity (19,20).…”
Section: Discussionmentioning
confidence: 97%
“…The N-terminal domain (1-147 residues) was shown to be essential for mitochondrial import and for maintenance of a folded active and malonyl-CoA-sensitive conformation (12)(13)(14). Functional analysis of natural and/or engineered mutations in CPT1A strongly contributed to understanding the catalytic and regulatory mechanisms implied in the acyltransferase family (15)(16)(17)(18)(19)(20). The recent three-dimensional structural models of the mouse and human carnitine acetyltransferase (CAT) provided critical insights into the molecular basis for fatty acyl chain transfer (21,22).…”
mentioning
confidence: 99%